(untitled) (Biological Sciences - PJSIR, 1999)
Infrared andLaser Raman spectraofthecompound, N-succinimydyI3-(2-pyridyldithio) proprionate (SPDP) andN- succinimydyl [3-(2-pyridyldithio) propionate]hexanote (LC-SPDP)arerecorded intheregion 100-4000 em:’. Afew observed bands areassignedtovariousmodesofvibrationsonthebasisofnormalcoordinate calculations assuming C, point groupsymmetry tothemolecules. Acomplete setofinternalcoordinates usedforthecalculations alsopresented.